Comportamento térmico do 8-quinolinol e seus nitro-derivados - Zorel Jr., Henrique E. [UNESP]; Costalonga, Ademir G. C. [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP] (Sociedade Brasileira de Química, 2001)
The compounds 5-nitro-8-quinolinol and 5,7-dinitro-8-quinolinol were obtained by nitration of the chelant 8-quinolinol. The compounds were characterized through EA, MNR, XRD, IR, TG, DTA and DSC. It was verified through thermal analysis that the compounds show consecutive processes of sublimation, fusion and vaporization. During the vaporization process, partial thermal decomposition was observed, with formation of carbonaceous residues. Considering a slower heating rate, the sublimation is the prevalent process to the nitro-derivatives while the vaporization is the main process to 8-quinolinol. The thermal stability follows the decreasing order from 5,7-dinitro-8-quinolinol to 5-nitro-8-quinolinol to 8-quinolinol.
Thermal behavior of the 8-quinolinol and their nitro-derivatives
Keywords: thermal behavior; 8-quinolinol; nitro-derivatives